Manajemen Mutu Pendidikan - Mohammad Ahyar Ma'arif (At- Ta'lim : Jurnal Pendidikan, 2016)
In accordance with its existence, man has always bernaluri to make a change that ultimately these changes will lead to progress in the reality of life good progress in the areas of technical and mechanical. Since then, the idea to do the transfer, preservation and development of human life as an effort to revamp that goes with synergies through management within a particular organization especially pendidian. Humans together and race each other to make a change, so management is becoming increasingly important role to deliver an educational institution in the creation of educational quality is better than before, and even can be said of management in education is the key of all forms of educational progress throughout the history of human civilization and the development of education. Management is an infra structures having a very significant role in formulating the institutional arrangements for reconstruction in improving the quality and the quality of education. In practical terms, the management of education must be improved to a better direction in its relevance for educational purposes as well as local institutional national education goals.